Clostridium and Cryptosporidium outbreak linked to a splash pad - Anna de Andrés Aguayo; Joan-Pau Millet; Laia Álvarez-Bruned; David Palma; Anna Gómez; Pau Gallés; Sara Sabaté; Gabriela Álvarez; Virginia Rodriguez; Thais Cornejo; Cristina Rius (BMC, 2024)
Abstract Background . Splash pads for recreational purposes are widespread. Using these pads can pose a health risk if they lack installation regulation and water quality supervision. Our aim was to describe a waterborne disease outbreak caused by Clostridium perfringens and Cryptosporidium spp. in a Barcelona district and the measures taken for its control. Methods . On August 2018, 71 cases of acute gastroenteritis were detected, affecting people who used a splash pad or were in contact with a user. Microbiological and environmental investigations were carried out. A descriptive analysis of the sample and Poisson regression models adjusted for age and sex were performed, obtaining frequencies, median values, and adjusted prevalence ratios with their 95% confidence intervals. Results The median age of the cases was 6.7 years, 27 (38%) required medical care, and three (4.2%) were hospitalized. The greater the number of times a person entered the area, the greater the number of symptoms and their severity. Nineteen (76%) of the 25 stool samples collected from cases showed the presence of one or both pathogens. Environmental investigations showed deficiencies in the facilities and identified the presence of both species in the splash pad. Health education and hygiene measures were carried out, and 14 days after the closure of the facilities, no more cases related to the pad were recorded. Conclusions . Specific regulations are needed on the use of splash pads for recreational purposes. Until these regulations are in place, these types of facility should comply with the regulations that apply to swimming pools and spas, including those related to the design of the tanks, water recirculation systems, and adequate disinfection systems.